Sorcery of thorns - Rogerson, Margaret (New York : Margaret K. McElderry Books, 2019)
When apprentice librarian Elisabeth is implicated in sabotage that released the library's most dangerous grimoire, she becomes entangled in a centuries-old conspiracy that could mean the end of everything.
Keywords: Apprentices -- Fiction; Libraries -- Fiction; Magic -- Fiction; Foundlings -- Fiction; Fantasy